Pyruvate kinase variant of fission yeast tunes carbon metabolism, cell regulation, growth and stress resistance. Issue 4 (22nd April 2020) - Kamrad, Stephan; Grossbach, Jan; Rodríguez‐López, Maria; Mülleder, Michael; Townsend, StJohn; Cappelletti, Valentina; Stojanovski, Gorjan; Correia‐Melo, Clara; Picotti, Paola; Beyer, Andreas; Ralser, Markus; Bähler, Jürg
Abstract: Cells balance glycolysis with respiration to support their metabolic needs in different environmental or physiological contexts. With abundant glucose, many cells prefer to grow by aerobic glycolysis or fermentation. Using 161 natural isolates of fission yeast, we investigated the genetic basis and phenotypic effects of the fermentation–respiration balance. The laboratory and a few other strains depended more on respiration. This trait was associated with a single nucleotide polymorphism in a conserved region of Pyk1, the sole pyruvate kinase in fission yeast. This variant reduced Pyk1 activity and glycolytic flux. Replacing the "low‐activity" pyk1 allele in the laboratory strain with the "high‐activity" allele was sufficient to increase fermentation and decrease respiration. This metabolic rebalancing triggered systems‐level adjustments in the transcriptome and proteome and in cellular traits, including increased growth and chronological lifespan but decreased resistance to oxidative stress. Thus, low Pyk1 activity does not lead to a growth advantage but to stress tolerance. The genetic tuning of glycolytic flux may reflect an adaptive trade‐off in a species lacking pyruvate kinase isoforms. Synopsis: This study shows that a single‐nucleotide polymorphism in the sole pyruvate kinase gene in Schizosaccharomyces pombe can explain the balance between respiration and fermentation, leading to substantial metabolic, regulatory and physiological adjustments. The laboratory S. pombe strain, together with a minority of natural isolates, features an unusual variant in a conserved region of its pyruvate kinase Pyk1, leading to a higher need for respiration. This variant reduces Pyk1 activity and the flux through glycolysis. Replacing the 'low‐activity' Pyk1 in the laboratory strain with the more common 'high‐activity' Pyk1 is sufficient to increase fermentation and decrease respiration. This metabolic reprogramming triggers systemic adaptations in the transcriptome and proteome, and in cellular traits, including increased growth and chronological lifespan, but decreased resistance to oxidative stress. Abstract : This study shows that a single‐nucleotide polymorphism in the sole pyruvate kinase gene in Schizosaccharomyces pombe can explain the balance between respiration and fermentation, leading to substantial metabolic, regulatory and physiological adjustments.